Producing Documentary Film to Promote Under Water Tourism in Thailand: Case Study, Petchburi Bremen Ship Wreck - Srifa, Kittithat (Siam Communication Review, 2022)
This research aims to study the production process of documentary film that promote under water tourism in Thailand; case study, Petchburi Bremen Ship Wreck. Also, this is a study guideline for studying other ship wreck in Thailand for historical education. The findings found that there are three steps in production process; preproduction, production and post-production. Preproduction, researching and gathering the data from reliable sources including interviews and documents then start writing the script. Production, to producing documentary film the researcher will have to interview the informants who are expert in ship wreck while the camera team are filming and following along with the researcher while working. For filming under water, the researcher must hire professional diver with high experience in filming under water. Post-production, the editing process, the researcher structures the story with content from the interview and deletes unnecessary content including mixing sound and insert graphics. The film has been broadcasting in YouTube since January 5th, 2021. The documentary film “Petchburi Bremen Ship Wreck” is broadcasting in online platform since it capable of engaging the target audience better than other type of media. Also, this learning media materials play a crucial role for learning the history before start diving.